1995
DOI: 10.1136/fn.73.1.f4
|View full text |Cite
|
Sign up to set email alerts
|

Low birthweight infants and total parenteral nutrition immediately after birth. I. Energy expenditure and respiratory quotient of ventilated and non-ventilated infants.

Abstract: The aim of this study was to determine the energy expenditure and respiratory quotient (RQ) of ventilated and nonventilated low birthweight infants during the first five days oflife, in order to determine optimal feeding regimens. Eighty six infants, of birthweight less than 1750 g, were grouped according to whether they were artificially ventilated or breathing air spontaneously, and whether they were parenteraily or enterally fed at the time of study. Energy expenditure and respiratory quotient were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…21,22 Sedation and muscle relaxation decrease Vo 2 and EE by reducing activity. 23 Moreover, neonates in the previous investigations had a wide range of gestational and postnatal ages. Values of Vo 2 and EE decrease with rising gestational age and increase with rising postnatal age.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Sedation and muscle relaxation decrease Vo 2 and EE by reducing activity. 23 Moreover, neonates in the previous investigations had a wide range of gestational and postnatal ages. Values of Vo 2 and EE decrease with rising gestational age and increase with rising postnatal age.…”
Section: Discussionmentioning
confidence: 99%
“…If energy and protein are not adequately provided by this alternative source, catabolism becomes inevitable. Data from the study conducted by Forsyth and Crighton [104] have revealed that to avoid catabolism total parenteral energy intake from day 1 of life needs to be 650 kcal/kg/day, including 1.0-1.5 g/kg amino acids. A higher energy intake decreases proteolysis to some extent and higher intakes of both protein and energy result in net protein anabolism [105].…”
Section: How Much Protein Is Needed By Infants Born At !30 Weeks Of Gmentioning
confidence: 99%
“…An infant's clinical status with associated hormonal and cytokine responses also need to be taken into account as they exert profound effects on protein metabolism in different body compartments, including increased production of certain (acute-phase) proteins and change in turnover of structural proteins, hence altered requirements for protein and amino acids as well as all other nutrients [106][107][108][109][110][111]. In spite of these illuminating nutrition study data from the study of Forsyth and Crighton [104] published in 1995, many clinicians still feel that protein administration in the first days of life in low gestation or sick newborns would not be tolerated, and many low gestation infants are not provided even such modest intravenous amino acids and energy during the first several days of life, virtually assuring the development and continuation of a catabolic state [77]. Even beyond the first few days of life, for a variety of reasons infants do not receive adequate protein or amino acids for several weeks.…”
Section: How Much Protein Is Needed By Infants Born At !30 Weeks Of Gmentioning
confidence: 99%
“…In reviewing these options, it is important to consider that fats provide the highest concentrated energy source relative to carbohydrates and have a lower respiratory quotient and thus lower production of carbon dioxide. 30 …”
Section: Poindexter and Martinmentioning
confidence: 97%